2023
DOI: 10.3390/nano13091458
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Carbon Nanotubes, Graphene, Fullerenes, and Dots

Abstract: The cytotoxicity of carbon nanomaterials is a very important issue for microorganisms, animals, and humans. Here, we discuss the issues of cytotoxicity of carbon nanomaterials, carbon nanotubes, graphene, fullerene, and dots. Cytotoxicity issues, such as cell viability and drug release, are considered. The main part of the review is dedicated to important cell viability issues. They are presented for A549 human melanoma, E. coli, osteosarcoma, U2-OS, SAOS-2, MG63, U87, and U118 cell lines. Then, important drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 158 publications
0
7
0
Order By: Relevance
“…Tissues and organs are sampled and subjected to histopathological examination, revealing any morphological changes indicative of cellular damage, inflammation, or necrosis. For a comprehensive analysis of the in vivo CNM cytotoxicity, readers are encouraged to refer to recent reviews, as this is a heavily examined topic in previous reviews. , …”
Section: Biomedical and Environmental Translation Of Cnmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissues and organs are sampled and subjected to histopathological examination, revealing any morphological changes indicative of cellular damage, inflammation, or necrosis. For a comprehensive analysis of the in vivo CNM cytotoxicity, readers are encouraged to refer to recent reviews, as this is a heavily examined topic in previous reviews. , …”
Section: Biomedical and Environmental Translation Of Cnmsmentioning
confidence: 99%
“…For a comprehensive analysis of the in vivo CNM cytotoxicity, readers are encouraged to refer to recent reviews, as this is a heavily examined topic in previous reviews. 1314,1315 There is a recent study performed to determine the cytotoxicity of CDs in vivo, where researchers found that CDs synthesized from sugar cane molasses at concentrations lower than 150 μg/mL had no impact on embryonic toxicity nor showed impediment on embryo development in zebrafish. 1316 Conversely, concentrations higher than 200 μg/mL greatly increased cytotoxicity, and demonstrated an impact on the dopamine levels, and a decrease in TH + neuronal cells.…”
Section: Cytotoxicity Of Cnmsmentioning
confidence: 99%
“…Along with the biomedical applications of carbon nanodots, there is great interest in using carbon nanomaterials in the agriculture sector [225,226]. This ranges from enhancement of crop productivity [227][228][229] to genetic alteration and acute cytotoxicity [230], nano-seed priming [231], and nano-remediation of polluted soil [232].…”
Section: Carbon Nanodotsmentioning
confidence: 99%
“…Despite the considerable efforts to characterize the potential neurotoxicity of carbon-based nanomaterials, [42,72,73] the results reported in the literature remain controversial, likely due to interstudy variations in size, physicochemical properties, and concentration. Here, to evaluate the cytocompatibility of both collagenimmobilized and suspended GlyCNDs with iPSC-derived NP spheroids, we carried out a colorimetric lactate dehydrogenase (LDH) assay complemented with propidium iodide (PI) live staining of dead cells.…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%